Edukacja kulturowa w opinii jej realizatorów - uczestników warsztatów w ramach projektu "Kultura Tędy" = Cultural education in the opinion of its providers - workshop participants within the "Kultura Tędy" project - Idzikowski, Bogdan; Mianowska, Edyta (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The study in this article is a diagnostic part of the Polish programme entitled "Bardzo młoda kultura", realized in the Lubuskie Voievodship within the "Kultura tędy" project. The research material comes from the second research round, and involves 25 participants of the training for cultural education providers, which took place in the summer of 2016 at Regionalne Centrum Animacji Kultury (the Regional Centre of Cultural Animation) in Zielona Gora. The study had a mixed, quantitative and qualitative, character. It was based on a questionnaire and an in-depth, focused interview.
Keywords: edukacja kulturowa; formy edukacji; sieci społeczne; kompetencje kulturowe; cultural education; forms of education; social networks; cultural competence